Transformational Leadership and Employee Engagement Analysis on Employee Performance Readiness to Change at Human Resources Development Agency - Ade Irni Rizka; Mahendro Sumardjo; Iwan Kresna Setiadi (Journal of Social Science, 2022)
In government organizations, demands for quality improvement and the use of information technology in services are unavoidable due to the expansion of globalization. Through improving employee performance during dynamic environmental changes, organizations can make this happen. This study aims to determine and analyze employee performance by looking at the effects of transformational leadership, employee engagement, and employee readiness to change. The respondents of this study were 73 employees at BPSDM Kumham who were selected by the purposive sampling method. The research method used is quantitative with data collection techniques through questionnaires—data analysis using Smart Partial Least Square (PLS) 3.0. The study results conclude that transformational leadership and employee engagement have a positive but not significant effect on employee performance. However, transformational leadership and employee engagement have a positive and significant effect on readiness to change. Readiness to change was found to have a positive and significant effect on employee performance and is a full mediator between the relationship between transformational leadership on employee performance and employee engagement on employee performance. Changes that occur both inside and outside the organization will not have an impact on employee performance if they have equipped themselves with the various competencies needed to carry out their work.